Interlayer excitons in transition metal dichalcogenide semiconductors for 2D optoelectronics - Liu, Yuanda (2022)
Optoelectronic materials that allow on-chip integrated light signal emitting, routing, modulation, and detection are crucial for the development of high-speed and high-throughput optical communication and computing technologies. Interlayer excitons in 2D van der Waals heterostructures, where electrons and holes are bounded by Coulomb interaction but spatially localized in different 2D layers, have recently attracted intense attention for their enticing properties and huge potential in device applications. Here, a general view of these 2D-confined hydrogen-like bosonic particles and the state-of-the-art developments with respect to the frontier concepts and prototypes is presented. Staggered type-II band alignment enables expansion of the interlayer direct bandgap from the intrinsic visible in monolayers up to the near- or even mid-infrared spectrum. Owing to large exciton binding energy, together with ultralong lifetime, room-temperature exciton devices and observation of quantum behaviors are demonstrated. With the rapid advances, it can be anticipated that future studies of interlayer excitons will not only allow the construction of all-exciton information processing circuits but will also continue to enrich the panoply of ideas on quantum phenomena.